1998 Advertising, media and public relations directory of the Philippines. (Makati City Diplomatic Post Pub., Corp., 1998)
This directory is an updated edition of the previous publication last 1996. It includes new and latest entries of communication networks around the country and Filipino tri-media abroad.
Cover title.
Keywords: Advertising -- Directories; Public relations -- Directories; Mass media -- Directories